PENGARUH PERBEDAAN WARNA CAHAYA LAMPU PETROMAKS TERHADAP HASIL TANGKAPAN IKAN UMPAN DENGAN ALAT TANGKAP PUKAT PANTAI (BEACH SEINE) DI TELUK AMBON BAGIAN DALAM - Rosihan Polhaupessy; H. La Nuhu; M. Syamsuddin (Universitas Teuku Umar, 2020)
This study attempts to identify the effects differences in the hues lamp oil-based lamps given to successful operations fish bait by the use of a get the beach ( seine seane ) on the gulf of ambon part in north conducted on 20 Oktober to 25 December 2018, the data was undertaken at night from pm 20.00 wit to 05.00 wit closer to waiheru coastal village ( i station ), coastal village and hunut station ( ii ) in as many as 10 times using two units of a get the beach ( seine seane ) and two a light color, treatment color the each green orens design and color on the random group ( RAK ). Remedial than 10 times there are three kinds of fish baited with the details are as follows: fish tatari ( rastrelliger spp ) 5927 the tail ( 44 % ) , heavy 10,42 kg ( 47 % ) , fish puri ( encrasicholine heteroloba ) the number of 6419 the tail ( 48 % ) , heavy 8,01 kg at 42 % and fish make ( sardinella sp ) the number of 1013 the tail ( 8 % ) , heavy 1,57 kg ( 11 % ) .With a total of the fish 13.395 a tail with heavy 20 kg with details of the fish a fish bait treatment with the greatest percentage in a lamp shade the color of orans namely 7745 a tail with heavy 9.99 kg and then treatment a lamp shade of a green color to the total number of 5614 a tail with heavy 9,98 kg .The results of the analysis of the results of the diversity of types of catch a fish bait , show that the two a light shade of have a which do not exhibit a significant difference or both the color of the light dicobakan the same - alike will be good for use in an effort to arrest a kind of small pelagic fish especially the types of a fish bait. Keyword : The light of a lamp , the catch, the gulf of ambon part in